Effect of government policy towards the abandoned housing project in Malaysia - Saidah An’nisaa, S.; Nur Farhayu, Ariffin; Nur Asyekin, R.; Mohamad Idris, Ali; Noram Irwan, Ramli (2019)
The issue of abandoned housing project happens across the globe, and it brings nothing positive to the stakeholders as well as to the economic and environment. Even though there are numerous policies and the Malaysian government has promulgated laws, yet the problem of abandoned housing projects is still occurring and not yet been fully addressed. The objectives are to investigate the factor of government policy that contribute to the abandoned housing project and to suggest the suitable solution in mitigating the problem. After the extensive literature review and multi-choice questionnaire survey method been done, the author found that the requirement of 30% low cost house for each development and unstandardized policy together with strict regulation from authorities is one of the main factor that contribute to the abandoned housing project. This paper suggested that the requirement of 30% low cost house for each development should be revised and the requirements for statutory approval should be standardized and short. This study will be contributing an information to the stakeholder involved in housing development.